Intermittent face cooling reduces perceived exertion during exercise in a hot environment - Miyazawa, T.; Mizutani, M.; Sheahan, J. P.; Ichikawa, D. (Journal of Physiological Anthropology, 2022)
Background: Facial cooling (FC) is effective in improving endurance exercise performance in hot environments. In this study, we evaluated the impact of intermittent short-lasting FC on the ratings of perceived exertion (RPE) during exercise. Methods: Ten healthy men performed 40 continuous minutes of ergometric cycle exercise at 65% of the peak heart rate in a climatic chamber controlled at an ambient temperature of 35 °C and a relative humidity of 50%. In the control (CONT) trial, the participants performed the exercise without FC. In two cooling trials, each participant underwent 10 s of FC at 2- (FC2) and 4-min (FC4) intervals while continuing to exercise. FC was achieved by applying two soft-gel packs (cooled to 0 °C) directly and bilaterally on the forehead, eyes, and cheeks. In another cooling trial, 10 s of FC was performed at 2-min intervals using two soft-gel packs cooled to 20 °C (FC2-20). Results: The RPE values in the FC4 trial were significantly lower than those in the CONT trial at 20 min (FC4, 11.6 ± 2.2 points; CONT, 14.2 ± 1.3 points; P < 0.01). Further, significant differences in the RPE values were observed between the FC4 and CONT trials at 5-15 min and 25-40 min (P < 0.05). RPE values were also significantly lower in the FC2 trial than in the CONT trial (5-40 min). Although the RPE values in the FC2-20 trial were significantly lower (5-10 min; 15-20 min) than those in the CONT trial, there were no significant differences in the RPE between the FC2-20 and CONT trials at 25-40 min. At 35 min, the RPE values were significantly higher in the FC2-20 trial than in the FC2 trial (P < 0.05). Conclusion: Intermittent short-lasting FC was associated with a decrease in RPE, with shorter intervals and lower temperatures eliciting greater attenuation of increase in the RPE.